Staphylococcal food poisoning from cream-filled cake in a metropolitan area of South-Eastern Brazil - Maria Lúcia Pereira; Luiz Simeão do Carmo; Elisângela José dos Santos; Merlin S. Bergdoll (Revista de Saúde Pública)
Twelve people became ill with vomiting and diarrhoea approximately four hours after eating cake with a cream filling at a birthday party and on the day following. The cake had been prepared by a food handler who had long experience in preparing foods for such functions. Staphylococcus aureus that produced enterotoxin A was isolated from the nose, the fingernails, and a healed infection on the neck of the food handler, and from the cake. Enterotoxin A was detected in the remaining portion of the cake. The cake, while still warm, had been refrigerated for one hour after it was prepared before it was removed for the party; it was refrigerated after the party. The cake was large (6 kg) and hence it was not adequately cooled in the hour during wich it was refrigerated before the party. The conclusion is that the cake was accidentally contaminated by the food handler and inadequately cooled before it was eaten.